Evaluation of hydrocarbon contaminants in olives and virgin olive oils from Tunisia. (May 2017) - Gharbi, Ines; Moret, Sabrina; Chaari, Olfa; Issaoui, Manel; Conte, Lanfranco S.; Lucci, Paolo; Hammami, Mohamed
Abstract: The present paper investigated on the presence of some hydrocarbon contaminants, namely polycyclic aromatic hydrocarbons (PAHs), mineral oil hydrocarbons (MOH) comprising saturated (MOSH) and aromatic (MOAH) compounds, and polyolefin oligomeric saturated hydrocarbons (POSH) in olives and extra virgin olive oils from Tunisia. Olive fruits were collected in sites exposed to different environmental contamination, and the oil extracted both by physical mean (using an Abencor extractor) and with solvent (using microwave assisted extraction, MAE). Analytical determination was performed by SPE cleanup on silica cartridge followed by spectrofluorometric detection, for PAH, and on-line HPLC-GC-FID for MOH and POSH. Oils extracted from olives by physical mean, as well as extra virgin olive oils from the market, had PAH levels never exceeding the EU legal limits. All olive samples showed similar MOSH profiles, but not clear correlation between the variable contamination levels and considered sources of contamination, was evidenced. The average MOSH content in oil extracted from olives by solvent (11.1 mg/kg) was about four time higher than in oil extracted by physical mean (2.6 mg/kg). MOSH in extra virgin oil from the market ranged from 10.3 to 38.0 mg/kg, while MOAH were not detected. The higher MOSH levels found in oils from the market evidenced an important contribution due to oil processing and/or packaging. Two of the samples were clearly contaminated with polyolefin oligomeric hydrocarbons (POSH) migrated from the plastic cap. Highlights: Determination of PAH and mineral oil in olives and extra virgin olive oil. Evaluation of background contamination in olive fruits. Migration of polyolefin oligomeric hydrocarbons (POSH) from plastic caps.